2017
DOI: 10.1155/2017/5348928
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Intracranial Hypertension: Prognostic Factors and Multidisciplinary Management

Abstract: Background Idiopathic intracranial hypertension (IIH) mostly affects young obese women and can lead to permanent visual impairment. However, prognostic factors and therapeutic strategy remain unclear. Methods We retrospectively collected data from all patients diagnosed and managed for IIH in our university center from January 2001 to December 2016. Results Seventy-nine patients were diagnosed with IIH. Bilateral transverse sinus stenosis (TSS) was found in 74% of the population. Visual outcome at 6 months was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 56 publications
5
36
0
Order By: Relevance
“…The mean opening CSF pressure at the time of diagnosis varies; in the current study, it was 38.2 cmH 2 O, which was similar to the result reported in Patsalides et al [14] study, which was 37 cmH 2 O. Chan [16] reported a higher value for the opening CSF pressure of 41.4 cmH 2 O; on the other hand, Smith and Friedman [17] and Chagot et al [15] obtained lower values, namely, 34.3 cmH 2 O and 28.5 cmH 2 O, respectively.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The mean opening CSF pressure at the time of diagnosis varies; in the current study, it was 38.2 cmH 2 O, which was similar to the result reported in Patsalides et al [14] study, which was 37 cmH 2 O. Chan [16] reported a higher value for the opening CSF pressure of 41.4 cmH 2 O; on the other hand, Smith and Friedman [17] and Chagot et al [15] obtained lower values, namely, 34.3 cmH 2 O and 28.5 cmH 2 O, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…IIH is common in overweight persons, and the mean body mass index of most studies was more than 25 kg/m 2 . In the current study, the mean body mass index was 33.2 kg/m 2 , and it was 35.4 kg/m 2 , 35 kg/m 2 , 34.8 kg/m 2 , and 27.1 kg/m 2 in Patsalides et al [14], Chagot et al [15], Saber et al [12], and Agarwal et al [13], respectively.…”
Section: Discussionmentioning
confidence: 44%
“…No significant impact of weight change on visual outcome was detected during follow‐up. Chagot et al have suggested that weight gain, rather than initial weight, is a leading factor of poor visual outcome in patients with IIH using first‐line treatment (Chagot et al, ). We propose that venous sinus stenting may be a powerful covariate that affects the outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that the trans-stenotic pressure gradient increased with escalating BMI prior to treatment and that baseline BMI was associated with the capacity of stenting to change intracerebral pressure and the trans-stenotic pressure gradient. (Chagot et al, 2017). We propose that venous sinus stenting may be a powerful covariate that affects the outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation